Analysis of Digital Marketing Strategy in the Era of the COVID-19 - Kartika Sari; Asyifa Anandya; Irsyad Kamal; Pandu Adi Cakranegara; Muhammad Aqshel Revinzky (Yayasan Ahmar Cendekia Indonesia, 2022)
The COVID-19 pandemic significantly affects the advancement of business entertainers in Indonesia. Business entertainers should track down the right technique to make due. One of the procedures during the pandemic is computerized showcasing, which permits business entertainers to advertise their items without being compelled by arrangements during the pandemic. Research on advanced promoting techniques for business entertainers to contend in this pandemic time utilizes subjective strategies with a logical distinct methodology. Expressive exploration is gathering information in light of the elements that help the object of examination. Subjective examination manages thoughts, insights, assessments, convictions of individuals to be contemplated and every one of them can't be estimated by numbers. The motivation behind the review was to discover how the procedures, components, cycles and exercises of business entertainers in utilizing advanced showcasing to contend during the pandemic. The aftereffects of the review show that there have been numerous business entertainers who have utilized advanced showcasing, which is 85%, as a methodology to expand deals and require a comprehension of computerized promoting. In view of exploration investigation, business entertainers who have utilized advanced showcasing can make due and even increment deals without depending on traditional stores.